BBK07, a Dominant In Vivo Antigen of Borrelia burgdorferi, Is a Potential Marker for Serodiagnosis of Lyme Disease - Coleman, Adam S. (American Society for Microbiology (ASM), 2009)
One of the recently identified Borrelia burgdorferi immunogens, BBK07, is characterized for its expression in the spirochete infection cycle and evaluated for its potential use as a serodiagnostic marker for Lyme disease. We show that the BBK07 gene is expressed at extremely low levels in vitro and in ticks but is dramatically induced by spirochetes once introduced into the host and is highly expressed throughout mammalian infection. In contrast, the expression of BBK12, a paralog of BBK07 with 87% amino acid identity, although expressed in vitro, remained undetectable in vivo throughout murine infection and in ticks. BBK07 is localized in the outer membrane, and the amino-terminal domain of the antigen is exposed on the microbial surface. A truncated BBK07 protein representing the amino-terminal domain is able to effectively detect antibodies to B. burgdorferi, both in experimentally infected mice and in humans. Further characterization of the immunodominant antigens of B. burgdorferi, such as BBK07, could contribute to the development of novel serodiagnostic markers for detection of Lyme disease.